Implementing Error Analysis Technique in ESL/EFL Teaching-Learning Activities: A Case Study in Saudi Context - DR AHMED BENYO (Research Journal in Advanced Humanities, 2025)
This study explores the written errors of Saudi secondary-level ESL/EFL learners as a means to evaluate and enhance English language teaching methodologies within the Kingdom’s educational framework. Grounded in the principles of error analysis, the research treats learner errors not as failures but as essential markers of the interlanguage development process. By analyzing written assignments from 50 students enrolled in public schools, the study identifies recurring grammatical inaccuracies, syntactic deviations, and lexical misuse, pointing to a limited mastery of English language rules despite its compulsory status in the national curriculum. A key finding is the pronounced influence of the learners’ first language, Arabic, which manifests through negative language transfer and structural interference, particularly in verb usage, sentence formation, and article application. These insights reveal the need for more nuanced, contrastive grammar instruction and culturally responsive pedagogical strategies that address the linguistic challenges specific to Arabic-speaking learners. Ultimately, the study affirms the value of error analysis as a diagnostic and corrective tool, capable of informing curriculum design, teacher training, and assessment practices aimed at improving English proficiency among Saudi learners.